2017
DOI: 10.2298/zmspn1733261b
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of indigenous Bacillus spp. isolated from soil

Abstract: Biocontrol using plant growth-promoting rhizobacteria (PGPR) represents an alternative approach to disease management, since PGPR are known to promote growth and reduce diseases in various crops. Among the different PGPR, members of the genus Bacillus are prefered for most biotechnological uses due to their capability to form extremely resistant spores and produce a wide variety of metabolites with antimicrobial activity. The objective of this research was to identify antagonistic bacteria for management of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In our previous study, we observed very strong antifungal activity of B. subtilis B5 and B7 against F. proliferatum BL5 (KX092461) and F. oxysporum f. sp. cepae BL7 (KX092466), while the antagonistic effect of Bacillus isolates toward F. verticillioides BL7 (KX092464) was not detected (Bjelić et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our previous study, we observed very strong antifungal activity of B. subtilis B5 and B7 against F. proliferatum BL5 (KX092461) and F. oxysporum f. sp. cepae BL7 (KX092466), while the antagonistic effect of Bacillus isolates toward F. verticillioides BL7 (KX092464) was not detected (Bjelić et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
“…Bacillus spp. were isolated from soil samples collected in several locations in Serbia as described by Bjelić et al (2017). Soil samples included the rhizosphere of plants, agricultural and non-agricultural soils, and differed in their physical and chemical properties, cropping and tillage history.…”
Section: Methodsmentioning
confidence: 99%